Organização histológica da glândula de cheiro do cateto (Pecari tajacu, Linnaeus 1758) e a influência da testosterona na manutenção de sua estrutura - Azevedo, Bruna Kaline Gorgonio de (2015)
The collared peccary (Pecari tajacu) belongs to the family Tayassuidae, have four digits on the forelimb and three in the pelvic limb, presents elongated snout and a short tail; stands out for having an odoriferous gland on the back that continuously secretes a whitish liquid. This secretion can be considered a chemical signal. Chemical signals intra-specific action are called phero mones acting in physiology and development of individuals or directly in their behavior. In several mammalian species, the function of the scent gland development is regulated by gonadal hormones. This study s objective was to describe the morphology of scent gland and assess if its structure is influenced by testosterone. For this we used twelve collared peccary from the Centro de Multiplicação de Animais Silvestres of the Universidade Federal Rural do Semi -Árido, divided into groups: group I (newborns peccary), group II (adult collared peccaries), group III (adult castrated collared peccaries), group IV (castrated collared peccaries and treated with testosterone). All the procedures used were approved by the UFERSA s Ethics in Animals Use Commission (pr ocess number: 26/2013). The collared peccary were sacrificed, the scent glands were dissected and the length and width dimensions were measured. Posteriorly glands fragments were subjected to histological processing, histomorphometric analyzes were performed, the proliferative kinetics of glandular cells were also evaluated through the AgNORs count method. The peccaries had a scent gland with oval shape and showed in the center a central duct. Two regions were distinct and differentiated by the color. The cranial portion was clear (sebaceous glands) and the caudal portion was dark (sweat gland). The newborn animal scent gland showed histological differences when compared to adult animal s glands and after castration the gland underwent a process of involution which can be partially reversed with hormone replacement. The sebaceous portion of the scent gland was the most affected by castration. The results of histomorphometric data and AgNOR count showed that the sebaceous portion of the collared peccary scent gland is under strong influence of testosterone, since the decrease in testosterone levels in the blood resulting from castration, generated low proliferative activity and changes significant in their secretory units